Peran Zakat Penghasilan dalam Membantu Membangun Pendidikan di Indonesia Khususnya Kabupaten Labuhan Batu Selatan - Yenni Samri Juliati Nasution; Muhammad Dzaki Abdillah; Siti Nurojiyah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Income zakat is a financial instrument with great potential in regional economic development, including in South Labuhanbatu Regency. This research aims to analyze the role of income zakat in improving community welfare and infrastructure development in the area. The method used in this research is a qualitative approach by collecting data through interviews, observation and documentation studies. The research results show that income zakat can make a significant contribution to social and economic programs, as well as encourage community participation in development. Therefore, effective zakat management can be one solution to overcome the problem of poverty and social inequality in South Labuhanbatu Regency.